Transit dosimetry in 192Ir high dose rate brachytherapy - Ade, Nicholas (My University, 2010)
Background and purpose: Historically HDR brachytherapy treatment planning systems ignore the transit dose in the computation of patient dose. However, the total radiation dose delivered during each treatment cycle is equal to the sum of the static dose and the transit dose and every HDR application therefore results in two radiation doses. Consequently, the absorbed dose to the target volume is more than the prescribed dose as computed during treatment planning. The aim of this study was to determine the magnitude of the transit dose component of two 192Ir HDR brachytherapy units and assess its dosimetric significance. Materials and Methods: Ionization chamber dosimetry systems (well-type and Farmertype ionization chambers) were used to measure the charge generated during the transit of the 192Ir source from a GammaMed and a Nucletron MicroSelectron HDR afterloader using single catheters of lengths 120 cm. Different source configurations were used for the measurements of integrated charge. Two analysis techniques were used for transit time determination: the multiple exposure technique and the graphical solution of zero exposure. The transit time was measured for the total transit of the radioactive source into (entry) and out of (exit) the catheters. Results: A maximum source transit time of 1.7 s was measured. The transit dose depends on the source activity, source configuration, number of treatment fractions, prescription dose and the type of remote afterloader used. It does not depend on the measurement technique, measurement distance or the analysis technique used for transit time determination. Conclusion: A finite transit time increases the radiation dose beyond that due to the programmed source dwell time alone. The significance of the transit dose would increase with a decrease in source dwell time or a higher activity source.
Keywords: transit/time/dose; HDR brachytherapy; HDR planning system; afterloader; ionization chamber dosimetry system; source configuration; multiple exposure technique